2009
DOI: 10.1109/tit.2009.2030488
|View full text |Cite
|
Sign up to set email alerts
|

Joint Wyner–Ziv/Dirty-Paper Coding by Modulo-Lattice Modulation

Abstract: The combination of source coding with decoder side information (the Wyner-Ziv problem) and channel coding with encoder side information (the Gel'fand-Pinsker problem) can be optimally solved using the separation principle. In this work, we show an alternative scheme for the quadratic-Gaussian case, which merges source and channel coding. This scheme achieves the optimal performance by applying a modulo-lattice modulation to the analog source. Thus, it saves the complexity of quantization and channel decoding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 34 publications
0
68
0
Order By: Relevance
“…Philosof and Zamir [10] employ coset codes for efficient communication over doubly dirty MACs and Gaussian version of this problem was studied using lattice codes in [11]. [12] and [13] propose lattice-based schemes for communicating over Gaussian multi-terminal networks. An achievable rate region based on Abelian group codes was provided for the general DSC problem in [14].…”
Section: Arxiv:14034583v2 [Csit] 13 Jan 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Philosof and Zamir [10] employ coset codes for efficient communication over doubly dirty MACs and Gaussian version of this problem was studied using lattice codes in [11]. [12] and [13] propose lattice-based schemes for communicating over Gaussian multi-terminal networks. An achievable rate region based on Abelian group codes was provided for the general DSC problem in [14].…”
Section: Arxiv:14034583v2 [Csit] 13 Jan 2015mentioning
confidence: 99%
“…In other words, we provide an example where codes built over groups outperform unstructured codes as well as codes built over finite fields. 13 Example 9: Consider a quaternary 3−to−1 IC with input and output alphabets X j = Y j = Z 4 = {0, 1, 2, 3} being the Abelian group of cardinality 4. Let ⊕ 4 denote the group operation, i.e., addition mod−4 in Z 4 .…”
Section: A Definitionsmentioning
confidence: 99%
“…The gap to the Wyner-Ziv bound is 6-7 dB, however, it is worth to stress that this bound assumes infinite dimensions in both the source and channel coding. In [16] it is in fact shown that MLM can reach the Wyner-Ziv bound as the lattice dimension goes to infinity.…”
Section: B Phase 2: Modulo-lattice Modulationmentioning
confidence: 99%
“…The idea of MLM originates from nested lattice codes in digital systems [17], [18] and was mentioned in [15] as a means of performing analog communication with side information. The idea is analyzed in [16] in a pointto-point scenario, where it is shown that MLM asymptotically reaches the Wyner-Ziv bound as the lattice dimension goes to infinity. Another motivation for MLM in situations where side information is available at the decoder can be found in [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, for side-information problems known as the "Wyner-Ziv" source and the "dirty-paper" channel, a nested pair of lattices is needed where one component lattice forms a good channel code while the other component lattice forms a good source code. For joint source-channel coding problems, lattices with a good NSM-VNR product are desired [34].…”
Section: Introductionmentioning
confidence: 99%